Coaching as a Tool of Managerial Support - Żukowska, Joanna (Coaching jako narzędzie wspierania kadry menedżerskiej, 2010)
The article serves as an introduction to coaching as empirical research. The main subjects of the study are the coaching definition, perfect coaching process, all the procedures and ways of dealing with coaching conversations. Moreover, the paper will present the skills of asking questions in coaching.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 237-246
Keywords: coaching; communication; process; employee; organization